Increase in transmitted resistance to non-nucleoside reverse transcriptase inhibitors among newly diagnosed HIV-1 infections in Europe. - Frentz, Dineke; Van de Vijver, David A M C; Abecasis, Ana B; Albert, Jan; Hamouda, Osamah; Jørgensen, Louise B; Kücherer, Claudia; Struck, Daniel; Schmit, Jean-Claude; Vercauteren, Jurgen; Åsjö, Birgitta; Balotta, Claudia; et al. (BMC Infect Dis, 2014)
BACKGROUND: One out of ten newly diagnosed patients in Europe was infected with a virus carrying a drug resistant mutation. We analysed the patterns over time for transmitted drug resistance mutations (TDRM) using data from the European Spread program. METHODS: Clinical, epidemiological and virological data from 4317 patients newly diagnosed with HIV-1 infection between 2002 and 2007 were analysed. Patients were enrolled using a pre-defined sampling strategy. RESULTS: The overall prevalence of TDRM in this period was 8.9% (95% CI: 8.1-9.8). Interestingly, significant changes over time in TDRM caused by the different drug classes were found. Whereas nucleoside resistance mutations remained constant at 5%, a significant decline in protease inhibitors resistance mutations was observed, from 3.9% in 2002 to 1.6% in 2007 (p = 0.001). In contrast, resistance to non-nucleoside reverse transcriptase inhibitors (NNRTIs) doubled from 2.0% in 2002 to 4.1% in 2007 (p = 0.004) with 58% of viral strains carrying a K103N mutation. Phylogenetic analysis showed that these temporal changes could not be explained by large clusters of TDRM. CONCLUSION: During the years 2002 to 2007 transmitted resistance to NNRTI has doubled to 4% in Europe. The frequent use of NNRTI in first-line regimens and the clinical impact of NNRTI mutations warrants continued monitoring.
Keywords: Adult; Anti-HIV Agents; Drug Resistance, Viral; Europe; Female; Genotype; HIV Infections; HIV-1; Humans; Male; Mutation; Phylogeny; Prevalence